$11 million from SAMHSA to train first responders and community groups on preventing OD deaths. Issue 33 (20th August 2021) - Knopf, Alison
Abstract : Last week, the Substance Abuse and Mental Health Services Administration (SAMHSA) distributed $11 million in grants to train first responders and community groups to prevent overdose deaths. The 13 grants were in training to administer naloxone.